The ethical challenges of palliative care from the perspectives of pediatricians: A qualitative study in Iran - Zahedi, Farzaneh; Kadivar, Maliheh; Khanali Mojen, Leila; Asadabadi, Mahsa; Tajalli, Saleheh; Ilkhani, Mahnaz; Barasteh, Salman; Elahikhah, Maryam; Larijani, Bagher (Frontiers in Pediatrics, 2022)
Background: Adherence to ethical principles is a requirement for palliative care delivery to children and a main concern of healthcare providers. Physicians usually face ethical challenges during their daily practice in hospitals and need adequate skills and the ability to identify and manage them. This study sought to explore the ethical challenges of palliative care from the perspectives of pediatricians. Methods: This qualitative study was conducted between April and July 2019 using the content analysis approach. Participants were fifteen pediatric medical residents, specialists, and subspecialists purposively recruited from pediatric hospitals in Tehran, Iran. Data were collected using in-depth semi-structured interviews and were analyzed using Graneheim and Lundman’s approach to conventional content analysis. Trustworthiness was ensured through the four criteria proposed by Guba and Lincoln. Results: Participants’ experiences of the ethical challenges of palliative care for children were grouped into two main categories, namely ‘bewilderment in dealing with children and their families’ (with two subcategories) and ‘conflicts in decision making’ (with three subcategories). The final five subcategories were: a) inability to effectively communicate with children and their families, b) inability to tell the truth about the disease, c) physician-parent conflicts, d) parent-child conflicts, and e) physician-physician conflicts. Conclusion: The main ethical challenges of palliative care from the perspectives of Iranian pediatricians are the inability to effectively communicate with children and their families, the inability to tell them the truth, and the inability to manage physician-parent, parent-child, and physician-physician conflicts. Identification and management of these challenges may help improve the quality of pediatric palliative care in Iran. Further studies are needed to confirm these findings in other settings.